2015
DOI: 10.7202/1032147ar
|View full text |Cite
|
Sign up to set email alerts
|

Un retour des patronymes au Québec, 2005-2010 : au-delà des chiffres, des discours complexes entre égalité, identité et filiation

Abstract: au-delà des chiffres, des discours complexes entre égalité, identité et filiation laurence charton*, louis duchesne**, denise lemieux* et françoise-romaine ouellette* Depuis 1981, le Code civil du Québec, dans la foulée de la reconnaissance du principe d'égalité des parents, permet d'attribuer à un enfant soit le nom de son père, soit le nom de sa mère, soit les deux noms réunis. La personne qui a reçu un nom composé peut le transmettre en totalité ou en partie à son enfant, combiné ou non avec le nom simple o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, our studies also show that people with a double surname most frequently pass one on to their child, especially when the father is the one with the double surname (Charton et al. 2015). The reasons they offered for transmitting only the father's surname also revealed that many of the women felt it was not important to hand their surname down to the child simply because of their relationship through pregnancy and childbirth.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…However, our studies also show that people with a double surname most frequently pass one on to their child, especially when the father is the one with the double surname (Charton et al. 2015). The reasons they offered for transmitting only the father's surname also revealed that many of the women felt it was not important to hand their surname down to the child simply because of their relationship through pregnancy and childbirth.…”
mentioning
confidence: 50%
“…For instance, in our previous studies on the transmission of surnames among heterosexual couples in Quebec (Charton and Lemieux 2015; Charton et al. 2015, 2017; Lemieux 2005), we noted that more than 30 years after the introduction of the law allowing parents the freedom to choose for their child either the surname of the father, the mother or both surnames, the vast majority of couples continue to use the father's surname (85 percent of couples in 2010). The reasons given for this are often related to anticipated difficulties in having a double surname, or the problems that their child might encounter when choosing a name for their own offspring.…”
mentioning
confidence: 93%